Processing Quantified Noun Phrases with Numbers Versus Verbal Quantifiers. Issue 2 (17th February 2018) - Moxey, Linda M.
ABSTRACT: Statements containing quantity information are commonplace. Although there is literature explaining the way in which quantities themselves are conveyed in numbers or words (e.g., many, probably ), there is less on the effects of different types of quantity description on the processing of surrounding text. Given that quantity information is usually conveyed to alter our understanding of a situation (e.g., to convey information about a risk), our understanding of the rest of the quantified statement is clearly important. In this article texts containing quantified statements expressed numerically versus verbally are compared in two text change experiments to assess how the entire quantified noun phrase is encoded in each case. On the basis of the results it is argued that numerical quantifiers place focus on the size of a subset, whereas verbal quantifiers are better integrated with nouns leading to more focus on the subset itself.